Modern approaches to monitoring the ecological condition of lake ecosystem waters - Yu. S. Tuchkovenko; V. А. Ovcharuk; М. О. Martyniuk; Ye. І. Gazyetov; О. V. Zotova; V. M. Khokhlov; D. Jiang; A. N. Tyler (Людина і довкілля: Проблеми неоекології)
Purpose. Presentation of the results of the implementation of new approaches to monitoring indicators of the ecological state of water in lake ecosystems using the example of the Danube lakes with the use of modern express methods of determining individual ecological parameters and satellite information of the water bodies' water bodies.